2020
DOI: 10.1007/s42770-020-00239-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness and novel sequence types of clinical Aeromonas dhakensis from Malaysia

Abstract: Aeromonas dhakensis is an emergent human pathogen with medical importance. This study was aimed to determine the sequence types (STs), genetic diversity, and phylogenetic relationships of different clinical sources of 47 A. dhakensis from Malaysia using multilocus sequence typing (MLST), goeBURST, and phylogenetic analyses. The analysis of a concatenated six-gene tree with a nucleotide length of 2994 bp based on six housekeeping genes (gyrB, groL, gltA, metG, ppsA, and recA) and independent analyses of single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The genomes for the A. dhakensis ST656 isolates generated in this present study are the first to be reported from striped catfish and are a welcome supplement to the relatively few genomes available for this species, compared to A. hydrophila . However, A. dhakensis is attracting increasing attention as an emerging pathogen with zoonotic potential, especially in Asia, where this species has been associated with serious infections and fatalities in humans (Huys et al, 2002 ; Wu et al, 2012 ; Chen et al, 2016 ; Khor et al, 2018 ; Kitagawa et al, 2019 ; Lau et al, 2020 ; Sun et al, 2021 ). Interestingly, though ST656 has been recovered exclusively so far from fish hosts, this clone was placed within a larger clonal complex of A. dhakensis strains originating from human clinical cases ( Figure 3 ), meaning outbreaks of disease due to A. dhakensis in fish hosts present a theoretical risk to susceptible individuals interacting with infected stocks.…”
Section: Discussionmentioning
confidence: 99%
“…The genomes for the A. dhakensis ST656 isolates generated in this present study are the first to be reported from striped catfish and are a welcome supplement to the relatively few genomes available for this species, compared to A. hydrophila . However, A. dhakensis is attracting increasing attention as an emerging pathogen with zoonotic potential, especially in Asia, where this species has been associated with serious infections and fatalities in humans (Huys et al, 2002 ; Wu et al, 2012 ; Chen et al, 2016 ; Khor et al, 2018 ; Kitagawa et al, 2019 ; Lau et al, 2020 ; Sun et al, 2021 ). Interestingly, though ST656 has been recovered exclusively so far from fish hosts, this clone was placed within a larger clonal complex of A. dhakensis strains originating from human clinical cases ( Figure 3 ), meaning outbreaks of disease due to A. dhakensis in fish hosts present a theoretical risk to susceptible individuals interacting with infected stocks.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 117 A. dhakensis isolates were retrieved from previous studies [ 7 , 8 , 9 , 10 , 11 , 12 , 22 ]. These isolates consisted of 94 clinical isolates from Malaysia and Singapore and 23 non-clinical isolates from Malaysia ( Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…A. dhakensis has been misidentified as A. hydrophila or A. caviae by phenotypic methods in the past decade. Our previous studies conducted since 2012 identified A. dhakensis as the predominant species (47/94, 50%) among clinical isolates in Malaysia by using a combination gene analysis of GCAT and rpoD genes, as well as multilocus sequence typing [ 7 , 8 ]. Following these studies, the presence of A. dhakensis was reported from aquatic sources in Malaysia, including multipurpose freshwater recreational lakes in Selangor [ 9 ], tank water of ornamental fish in Klang Valley [ 10 ], food fish in East Malaysia [ 11 ] and as clinical isolates of A. dhakensis in Singapore [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sequence identity matrix analysis was performed with BioLign software ver. 4.0.6.2 ( Lau et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%